PANDANGAN ULAMA TERHADAP DAKWAH SALAFIYAH - Muhammadin Muhammadin (JIA (Jurnal Ilmu Agama), 2017)
Salafi is the generation of the prophet’s companions and two generations afterwards. Salafi was born and developed from circle studies. They live naturally, and continue from generation to generation until now. The salafi dakwah is based on two principles: Tashfiyah and Tarbiyah which means purification and education. Salafiyah propaganda invites to aqidah and true worship, invites to study the scriptures of Islamic scholars and calling for tauhid (oneness of God). The focus of the propaganda always on what the Prophet taught, based on the understanding of the companions who in fact are the most knowledgeable about Islam. The emergence of the stern attitude of this salafi da'i is linked on two things: Firstly, this salafi prophecy is consistent and firmly stating between the haq and the wrong. Secondly, the mission of salafi upholds the principle of tashfiyah (Purification). The salafi dakwah is very consistent with the refinement of Islamic teachings. And it is very natural that there are teachings outside of Islam that are mixed in Islam must be rejected.